Emissivity Measurements and Laboratory Intercalibration at PSF of Oxford University and PEL of DLR - Maturilli, Alessandro; Bowles, Neil; Thomas, Ian R.; Helbert, Jörn (2013)
Emissivity spectra of analogue materials are needed for the analysis of remote sensing emission spectra of airless surfaces. The increasing number of planetary missions to the Moon, Mercury, asteroids, and other minor bodies require appropriate laboratory set-ups to fulfill those requirements. Two independent groups, one at Oxford University and the other at the German Aerospace Center (DLR) in Berlin provide suitable chambers for emissivity measurements in vacuum. The Planetary Spectroscopy Facility (PSF) of the Oxford University favored a high vacuum, low to average sample temperatures, and a limited spectral range for measurements, mostly inspired from lunar and asteroids environment. At the Planetary Emissivity Laboratory (PEL) of DLR, the set-up allows measuring in low-moderate vacuum, for sample tem-peratures from low to very high (> 1000 K) and in an extended spectral range (1 to over 100µm), with Mercury being the principal driver of chamber design. To understand the influence of environment parameters on emissivity spectra, we measured a fine (0-25 µm) sample of volcanic dust from Iceland (PEL ID 00000240) under several environmental conditions at PSF, and for comparison under standard conditions at PEL.